2008
DOI: 10.1254/jphs.fp0071422
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Effect of Rebamipide on Aspirin-Induced Gastric Lesions and Disruption of Tight Junctional Protein Zonula Occludens-1 Distribution

Abstract: Abstract. Aspirin and nonsteroidal anti-inflammatory agents are known to induce gastroduodenal complications such as ulcer, bleeding, and dyspepsia. In this study, we examined the prophylactic effect of rebamipide, an anti-ulcer agent with free-radical scavenging and antiinflammatory effect, on acidified aspirin-induced gastric mucosal injury in rats. In addition, we investigated the mucosal barrier functions disrupted by aspirin. Oral administration of acidified aspirin resulted in linear hemorrhagic erosions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 59 publications
(33 reference statements)
1
13
0
10
Order By: Relevance
“…It has been shown in conventional mice that intra-colonic administration of trypsin cause mucosal damage [29] whereas high levels of intra-colonic trypsin in germfree animals never trigger any mucosal damages [4], [30], [31], [32], [33], [34]. Obviously, there is a need for “trigger” microbe(s) or mechanism(s).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in conventional mice that intra-colonic administration of trypsin cause mucosal damage [29] whereas high levels of intra-colonic trypsin in germfree animals never trigger any mucosal damages [4], [30], [31], [32], [33], [34]. Obviously, there is a need for “trigger” microbe(s) or mechanism(s).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of LDA and/or NSAID leads to hyper-permeation of small intestinal mucosa [10]. Moreover, chronic hyper-permeation in the small intestinal mucosa leads to rhexis of tight junction [15]. On the other hand, reducing prostaglandin leads to decreasing of blood flow [16].…”
Section: Discussionmentioning
confidence: 99%
“…Matsubara et al [45] reported that intact (45 kDa) and truncated (40 kDa) forms of OVA were detected in portal and peripheral blood after oral administration, indicating that OVA absorbed into blood from the intestinal lumen possesses its allergenicity. With regard to the mechanism of ASP-induced intestinal barrier disruption, suppression of prostaglandin synthesis by COX-1 [46] , oxidative stress [47] , and modulation of tight junctional proteins such as zonula occludens (ZO)-1 [48] and claudin-7 [49] have been reported. The specific sensitization is known to increase intestinal absorption of the allergen in several animal models of allergy [50][51][52][53][54] .…”
Section: Discussionmentioning
confidence: 99%